Office Productivity in Computerized Settings:: The Role of Machine Statistics, Performance Feedback and Job Experience - Chalykoff, John; Nohria, Nitin (Journal of Comparative International Management, 1998)
This paper develops and tests a model of the determinants of productivity in twenty computerized offices of the Internal Revenue Service. The results suggest first, that management's focus on machine monitoring statistics is misguided; second, that performance feedback has a significant effect on productivity; and third, that job experience plays a central role in productivity even in entry-level positions.